College Student’s Comprehension on Te Iru Aspects - Tasman, Annisa Qamara; Rahayu, Nana; Budiani, Dini (KIRYOKU, 2021)
This research is a study that discusses the college student’s comprehension on te iru aspect using 7 indicators of comprehension include interpreting, exemplifying, classifying, summarizing, inferring, comparing, and explaining. This researsch is focused on the progressive aspect, habituative aspect, and resultative aspect. The purpose of this study is to describe students' comprehension of te iru aspects. The method used in this study is qualitative descriptive. Data was obtained from interviews with 8 Japanese college students. The results showed that student’s comprehension of all three aspects of te iru is not perfect. The highest order of comprehension on te iru aspects starts from progressive, habituative, and resultative aspect.